2016
DOI: 10.4191/kcers.2016.53.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Bloating Mechanism of Lightweight Aggregate with the Size

Abstract: The purpose of this study was to investigate the bloating mechanism of artificial lightweight aggregates with different sizes (ESA, effective surface area). Aggregates were produced using hard clay, stone sludge, and a bloating agent in order to observe the effect of the gradation of the artificial lightweight aggregates. Kerosene and amorphous carbon were used as bloating agent. The particle size of the produced aggregate ranged from 3 mm to 9 mm. With regard to the amount of bloating agent to be used, 2 ~6 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…This is thought to be related to the viscous behavior of the aggregate; at higher temperatures, viscous behavior increases due to increases in the liquid phase. Lee et al [10] and Kang et al [13] also found that the aggregate density was lower at higher temperatures. The density decreased as the soaking time at the bloating activation temperature increased, but the density decreased after 10~20 minutes, with no significant difference between 20 and 40 minutes.…”
Section: Bloating Activation Processmentioning
confidence: 92%
See 2 more Smart Citations
“…This is thought to be related to the viscous behavior of the aggregate; at higher temperatures, viscous behavior increases due to increases in the liquid phase. Lee et al [10] and Kang et al [13] also found that the aggregate density was lower at higher temperatures. The density decreased as the soaking time at the bloating activation temperature increased, but the density decreased after 10~20 minutes, with no significant difference between 20 and 40 minutes.…”
Section: Bloating Activation Processmentioning
confidence: 92%
“…Studies of sintering variables have been conducted worked various methods. Different studies have investigated various sintering methods, including rapid sintering [10,11], two-step sintering [12], and normal sintering [1,13]. Riley [1] reported that most clays were expanded by rapid sintering, and defined the chemical composition for the production of lightweight aggregates through the normal sintering process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…74,75 A possible explanation for the reduction of hematite into wuestite (FeO) that could occur at a temperature range between 1100°C and 1160°C is the formation of liquid phase on the LWA surface that could hinder oxygen diffusion and create a reducing atmosphere in the LWA core, thus leading to hematite reduction. 7,76 In this study, the unburned carbon content for NV and WP ashes was small (0.12% and 0.19%, respectively), and complete oxidation of carbon in the form of CO 2 and CO release would happen at temperatures below 1000°C 29 (see Figures 5 and 6), which had some overlap with the temperature at which the liquid phase started to form (see Figure 3). This indicates that there could have been some contribution from Figure 15 presents a holistic view of each LWA to provide the required conditions (liquid phase quantity, viscosity value, and emitted gas amount) during sintering for successful production of spherical LWA.…”
Section: Formation Of Gaseous Phase During Sinteringmentioning
confidence: 70%
“…ese various wastes were utilized, and various methods of sintering were used. Riley [14] and Kang and Kang [15] used a temperature elevation sintering method, and Lee [16,17] used rapid sintering. And the aggregate was sintered in the study of Lee [18] by the two-stage sintering method.…”
Section: Introductionmentioning
confidence: 99%